Prevalence of zoonotic parasites in an endangered Iberian wolf (Canis lupus signatus) population in Portugal - Figueiredo, Ana M.; Barros, Tânia; Valente, Ana M.; Fonseca, Carlos; Madeira de Carvalho, Luís; Tinoco Torres, Rita (Mammalian Biology, 2019)
As a top predator, the Iberian wolf (Canis lupus signatus) plays a major role shaping interactions within food webs. Due to its conservation status in Portugal, i.e. endangered, it is important to understand the role of parasites in this population, since they can be a limiting factor for the population fitness and trophic interactions and, ultimately, their survival. From November 2017 to August 2018, 33 fresh faecal samples were collected in several transects distributed throughout Montesinho Natural Park. Samples were analysed by means of four coprological techniques. A total of three helminth parasites (Ancylostoma spp., Uncinaria spp. and Eucoleus aerophilus) were identified based on size and morphology. The overall prevalence was low (15.5%), being Ancylostoma spp. the most prevalent parasite. The three parasites found are of major concern, once they are pathogenic to humans and other wild and domestic animals. We suggest surveillance programs that include both parasite and wildlife monitoring. To our knowledge, this is the first coprological study performed with this Iberian wolf population. R.T. Torres and A. M. Valente were supported by a post-doctoral and PhD grants from FCT, respectively SFRH/BPD/112482/2015 and SFRH/BD/127817/2016, co-financed by the European Social Fund POPH-QREN program. This research was also financially supported by the project POCI-01-0145-FEDER-030310- funded by FEDER, through COMPETE2020 - Programa Operacional Competitividade e Internacionalização (POCI), and by national funds (OE), through FCT/MCTES. We would like to thank University of Aveiro (Department of Biology) and FCT/MEC for the financial support to CESAM (UID/AMB/50017/2019) through national funds and, where applicable, co-financed by the FEDER, within the PT2020 Partnership Agreement. CIISA-FMV-ULisboa, under project UID/CVT/00276/ 2019 (FCT), provided additional funding. Peer reviewed